Inclusive School Management in Project-Based Learning Implementation: A Case Study in Kindergarten Settings - Purnamawati, Purnamawati; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Implementation of inclusive education at the kindergarten level faces complex challenges in managing learning that accommodates student diversity. Project-Based Learning (PBL) emerges as a promising pedagogical approach for inclusive environments, yet empirical research on optimal management strategies to support PBL implementation in inclusive early childhood settings remains limited. This study employed a qualitative descriptive design conducted over three months (April-June 2025) at Taman Kanak-Kanak Kongbeng, East Kalimantan. Data were collected through semi-structured interviews with key stakeholders, direct classroom observations, and documentation analysis. Data validity was ensured through triangulation and member checking procedures. Findings indicate that inclusive school management can effectively support PBL implementation through systematic collaborative approaches involving administrators, classroom teachers, special education teachers, and parents. PBL implementation in inclusive settings enhanced both social and academic skills of all students, including children with special needs. Effective strategies included flexible project design, differentiated instruction, and authentic assessment focusing on learning processes. Results confirm that well-managed inclusive PBL environments can create positive outcomes for all students. Successful implementation requires ongoing teacher training, clear inter-staff coordination, and adequate resource allocation to support inclusive education infrastructure.